2017
DOI: 10.1186/s12886-017-0571-7
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors, diagnosis and management of Acanthamoeba keratitis in a referral Center in Southern China

Abstract: BackgroundTo analyse the associated factors, diagnosis, clinical manifestations and therapeutic effects of Acanthamoeba keratitis at a tertiary ophthalmic centre in Southern China.MethodsA retrospective clinical study was performed in fifteen patients who were admitted to Zhongshan Ophthalmic Centre (ZOC) from January 2004 to December 2014. The patients’ pathogenesis-associated factors were analysed, and preoperative diagnoses were determined using corneal scraping cultures and/or confocal microscopy followed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
(27 reference statements)
0
28
0
Order By: Relevance
“…Reviews have shown that AK is a rare but severe corneal infection 13,63 caused by the species Acanthamoeba. 4,22,[64][65][66][67][68][69] It is painful and difficult to diagnose and treat 1,5 and can lead to blindness or even enucleation. 16,20,28,32,34,38,56,[70][71][72][73] The devastating risk of vision loss is connected to scarring and corneal ulceration, 74 causing massive ocular injury.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews have shown that AK is a rare but severe corneal infection 13,63 caused by the species Acanthamoeba. 4,22,[64][65][66][67][68][69] It is painful and difficult to diagnose and treat 1,5 and can lead to blindness or even enucleation. 16,20,28,32,34,38,56,[70][71][72][73] The devastating risk of vision loss is connected to scarring and corneal ulceration, 74 causing massive ocular injury.…”
Section: Definitionmentioning
confidence: 99%
“…88 AK cases in China may also be related to soil-contaminated matter and corneal trauma. 65 Lorenzo-Morales et al noted that between 1980 and 1990, the incidence of AK worldwide was relatively low, at 1-2 cases per million CL wearers, 16 while the relationship between the use of CLs and AK was first established in 1984. 31 With a rise in the number of CL wearers, a direct increase of reported cases was observed.…”
Section: Incidencementioning
confidence: 99%
“…Acanthamoeba keratitis is a rare and vision-threatening condition [1]. The clinical picture may be various but some findings are believed to be typical: the unilateral presentation, a history of CL wearing, diffuse corneal haze, radial keratoneuritis and a ring-shaped stromal infiltrate [1,2,4]. Among symptoms, blurred vision and disproportionate pain are frequently reported, with the latter being largely considered pathognomonic of AK [11].…”
Section: Discussionmentioning
confidence: 99%
“…Soft CL are known to be at increased risk than rigid gas permeable (RGP) lenses [2]. AK may have a proteiform presentation [3,4]. At the onset, signs and symptoms are often aspecific and the clinical picture may be mistaken as a fungal, bacterial or viral infection leading to a delay in the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The number of infection cases is increasing every year owing to the increase in the number of contact lens wearers who do not comply with recommended hygiene practices and even rinse their contact lenses with tap water [4,5]. Additionally, an increase in the number of cases of AK has been reported in China [6]. Because of all the threats and their dangerous effects on human health, the early detection of pathogenic Acanthamoeba in environments is essential.…”
mentioning
confidence: 99%